Inferior turbinate osteoma: a case report - Gill, Manmeet Kaur; Gole, Sheetal G.; Rana, Shweta; Garg, Shilpa; Kalhan, Shivani (International Journal of Research in Medical Sciences, 2017)
Osteoma is the most common benign tumor of the paranasal sinuses. Turbinate osteomas are very rare and only five middle turbinate, two inferior turbinate and one superior turbinate osteoma cases have been reported. We present a rare case of osteoma of the left inferior turbinate in a patient presented with unilateral nasal obstruction that was removed endoscopically and conduct a literature review on turbinate osteomas arising from different turbinates.